Convergence of regenerative medicine and synthetic biology to develop standardized and validated models of human diseases with clinical relevance. (December 2015) - Hutmacher, Dietmar Werner; Holzapfel, Boris Michael; De-Juan-Pardo, Elena Maria; Pereira, Brooke Anne; Ellem, Stuart John; Loessner, Daniela; Risbridger, Gail Petuna
Graphical abstract: Highlights: The development of clinically relevant disease models requires systems biology expertise. 3D in vitro model systems make more effective predictions of results in human medicine. TE&RM strategies offer great potential to enhance humanized murine model systems. Tissue engineering concepts facilitate personalized diagnostic and therapeutic strategies. Abstract : In order to progress beyond currently available medical devices and implants, the concept of tissue engineering has moved into the centre of biomedical research worldwide. The aim of this approach is not to replace damaged tissue with an implant or device but rather to prompt the patient's own tissue to enact a regenerative response by using a tissue-engineered construct to assemble new functional and healthy tissue. More recently, it has been suggested that the combination of Synthetic Biology and translational tissue-engineering techniques could enhance the field of personalized medicine, not only from a regenerative medicine perspective, but also to provide frontier technologies for building and transforming the research landscape in the field of in vitro and in vivo disease models.